Subjective Aging and Objectively Assessed Hearing Function: A Prospective Study of Older Adults. (29th January 2022) - Stephan, Yannick; Sutin, Angelina R; Terracciano, Antonio
Abstract: Objectives: Subjective aging is consistently related to a range of health-related outcomes, but little is known about its relationship with sensory functioning. The present prospective study tested whether subjective age and self-perceptions of aging (SPA) are associated with objective hearing function. Methods: Participants were 7, 085 individuals aged 50–93 years (60% women, mean = 65.15, standard deviation [ SD ] = 8.71) from the Health and Retirement Study. Measures of subjective age, SPA, and information on demographic factors were obtained in 2008/2010. Objective hearing function was assessed 8 years later in 2016/2018. Furthermore, potential mediating variables (C-reactive protein, body mass index, physical inactivity, and chronic conditions) were assessed in 2012/2014. Results: In regression analyses that accounted for demographic factors, older subjective age and negative SPA were associated with lower hearing acuity 8 years later. In addition, 1 SD older subjective age and negative SPA were related to a 9% and 7% higher likelihood of hearing impairment. Mediation analyses revealed that physical inactivity and chronic conditions partially mediated subjective age and SPA associations with hearing acuity. There was little evidence that the link between subjective aging and hearing was moderated by hearing aids and partial support for a moderating role of age. Discussion: This study provides new evidence that subjective aging is prospectively related to hearing function. Individuals with older subjective age or negative SPA have unfavorable behavioral and clinical profiles that explain part of their lower hearing function. Individuals' experience with their aging process is a marker of risk for impaired hearing.